Long Noncoding RNA Can Be a Probable Mechanism and a Novel Target for Diagnosis and Therapy in Fragile X Syndrome - Huang, Ge; Zhu, He; Wu, Shuying; Cui, Manhua; Xu, Tianmin (Frontiers in Genetics, 2019)
Fragile X syndrome(FXS) is most common congenital hereditary disease of low intelligence after Down Syndrome. Its main pathogenic gene is Fragile X mental retardation 1 (FMR1) gene associated with intellectual disability, autism and Fragile X-related primary ovarian insufficiency (FXPOI) and Fragile X-associated tremor/ataxia syndrome (FXTAS). Fmr1 gene transcription leads to the absence of fragile X mental retardation protein (FMRP). How to relieve or cure disorders associated with FXS has also become a clinically disturbing problem. Previous studies have recently shown that Long noncoding RNAs (lncRNA) contribute to the pathogenesis. And it has identified that several lncRNAs including FMR4, FMR5 and FMR6 contribute to developing FXPOI/FXTAS, originating from the FMR1 gene locus. FMR4 is a product of RNA polymerase II and can regulate the expression of relevant genes during differentiation of human neural precursor cells. FMR5 is a sense-oriented transcript while FMR6 is an antisense lncRNA produced by the 3’UTR of FMR1, being likely to contribute to developing FXPOI, and it overlaps exons 15–17 of FMR1 as well as two microRNA binding sites. Additionally, BC1 can bind FMRP to form inhibitory complex and lncRNA TUG1 also can control axonal development by directly interacting with FMRP through modulating SnoN–Ccd1 pathway. Therefore, these lncRNAs provide pharmaceutical targets and novel biomarkers. This review will 1) describe the clinical manifestations and traditional pathogenesis of FXS and FXTAS/FXPOI. 2) summarize what is known about the role of lncRNAs in the pathogenesis of FXS and FXTAS/FXPOI. 3) provide an outlook of potential effects and future directions of lncRNAs in FXS and FXTAS/FXPOI researches.